The ethics of migration research methodology: dealing with vulnerable immigrants - Liempt, Ilse van; Bilger, Veronika (Sussex Academic Press, 2009)
Methodological issues for the study of migrant incarceration in an era of discretion in law in the southern USA / Robert F. Barsky -- Multi-perspective research on foreigners in prisons in Switzerland / Christin Achermann -- Different methods to research irregular migration / Richard Staring -- Challenges and strategies in empirical fieldwork with asylum seekers and migrant sex workers / Janine Dahinden and Denise Efionayi-Mäder -- Methodological and ethical dilemmas in research among smuggled migrants / Veronika Bilger and Ilse van Liempt -- The "insider" position : ethical dilemmas and methodological concerns in researching undocumented migrants with the same ethnic background / Eugenia Markova -- The fieldworker as social worker : dilemma's in research with Moroccan unaccompanied minors / Nuria Empez